2021
DOI: 10.1097/mlr.0000000000001574
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Disenrollment From Medicare Advantage Plans Are Higher for Racial/Ethnic Minority Beneficiaries

Abstract: Background: Each year, about 10% of Medicare Advantage (MA) enrollees voluntarily switch to another MA contract, while another 2% voluntarily switch from MA to fee-for-service Medicare. Voluntary disenrollment from MA plans is related to beneficiaries’ negative experiences with their plan, disrupts the continuity of care, and conflicts with goals to reduce Medicare costs. Little is known about racial/ethnic disparities in voluntary disenrollment from MA plans. Objective: The objective of this study was to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The levels of disenrollment that we measured are larger than in previous studies that only focused on 1-year disenrollment . On one hand, these levels of disenrollment may be indicative of a healthy MA marketplace, with beneficiaries freely choosing contracts and making different elections if better choices become available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of disenrollment that we measured are larger than in previous studies that only focused on 1-year disenrollment . On one hand, these levels of disenrollment may be indicative of a healthy MA marketplace, with beneficiaries freely choosing contracts and making different elections if better choices become available.…”
Section: Discussionmentioning
confidence: 99%
“…A key feature of MA is that beneficiaries may choose from a wide variety of plans in their markets and may change their enrollment on an annual basis. Prior work has found that annual disenrollment rates from MA plans are higher for beneficiaries with greater health needs . However, little is known about disenrollment over a longer term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, controls for observable differences between the beneficiaries in MA and TM does not account for differences in the patient populations that may be unobserved and related to dementia diagnosis. Third, beneficiaries in MA plans may switch to TM, with higher rates of switching for racial and ethnic minority groups 17 . We quantified dementia prevalence and incidence by race and ethnicity for beneficiaries in MA 2017 and did not restrict them to MA in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Conducting randomized controlled trials (RCTs) to understand how life-sustaining interventions might lead to different outcomes across racial and ethnic groups is both unethical and impracticable. These types of research questions are best answered using observational data, but there are limitations to databases such as claims registries, which often lack important clinical details 10,11 . With the development of high-resolution datasets such as MIMIC-IV, we can apply a causal inference framework to leverage this real-world data in understanding how different patients have been affected by different interventions 12 .…”
Section: Introductionmentioning
confidence: 99%